VARIATIONS IN THE ELECTROPHORETICALLY SEPARATED ACID PHOSPHATASES OF TETRAHYMENA - Sally Lyman Allen; Margaret S. Misch; BARBARA M. MORRISON (1963)
The acid phosphatases of variety 1 of Tetrahymena pyriformis can be separated into 17 zones by electrophoresis in starch gels of pH 7.5. All of these acid phosphatases have an optimal pH of about 5.0 and are inhibited by 10 mM sodium fluoride on d-tartaric acid. With one exception, all hydrolyze sodium α-naphthyl acid phosphate. Differences between the acid phosphatases are observed in their ability to hydrolyze other substrates using either the coupling technique or a modification of the Gomori-lead method. Inhibition of 2 of the acid phosphatases occurs in the presence of 1 mM of Mn ++ or Zn ++ ; 0.1 mM of p-chloromercurobenzoic acid inhibits these and others. Variations between the acid phosphatases were observed under different growth conditions and in their distribution in various cell fractions. A major variation in the acid phosphatases that is under genetic control occurs in extracts of different genotypes. The results suggest that the electrophoretically separated acid phosphatases are a family of enzymes that vary in their degree of relationship. Some are different enzymes. Others are more closely related and represent variations of a single enzyme; i.e., mutant forms produced by different alleles, hybrid forms produced by interaction of alleles, and isozymes produced by a single gene. Most of the acid phosphatases are probably associated with lysosomes, although one appears to be associated with microsomes. This acid phosphatase is much more active in synthetically grown cells than in cells grown in proteose-peptone or in bacterized medium. It does not hydrolyze sodium β-glycerophosphate.